Dark triad personality traits and perfectionism in Peruvian university students: a network analysis - Cristian Ramos-Vera (BMC Psychology, 2025)
Abstract Background Although studies on the dark triad and perfectionism have been conducted in different regions, most rely on correlational or regression approaches and rarely explore these traits using psychological network analysis. Furthermore, few investigations have examined the role of sociodemographic variables, such as gender and age, in shaping these associations. Objective In this study, the relationship between the Dark Triad and perfectionism in Peruvian university students was analyzed by means of psychological network analysis including variables such as gender and age. Methods The sample consisted of 515 university students between 20 and 30 years of age (56.7% male). In this study, the Dark Triad Short Scale and the Multidimensional Brief Perfectionism Scale were used. Results The results of the study revealed a positive association between Machiavellianism and perfectionistic strivings and concerns. In addition, psychopathy was found to be associated with perfectionistic concerns, whereas narcissism showed a relationship with perfectionistic strivings. Likewise, a stronger association was observed between Machiavellianism and men, while perfectionistic strivings were directly correlated with age. Finally, psychopathy was found to be the most central dimension in the network, showing a strong interconnection with narcissism and perfectionistic concerns. Conclusion These results provide further insight into the complex interaction between aversive traits and goal-oriented traits, both adaptive and maladaptive, in university students.